Erlebte Authentizität: diskursive Herstellung von Authentizität zwischen Performanz und Zuschreibung - Schwidlinski, Pierre (Sprache und Wissen, 2020)
A range of disciplines have described different access points to authenticity, but until now, there has been no empirical, discourse-linguistic investigation of authenticity. Personal authenticity is always linked to its social and situational performance but is manifested first and foremost in the attribution of authenticity. This study presents a systematic analytic model of the discursive creation of (non-)authenticity in the public sphere.
Titel der Dissertation: Die Herstellung von Authentizität zwischen Performanz und Zuschreibung
Keywords: Hochschulschrift; Performativität; Authentizität; Diskurs; Zeitungstext; Deutsch